2009
DOI: 10.1016/j.compchemeng.2009.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of paradigms for modelling integrated supply chains

Abstract: Contemporary problems in process systems engineering often require model-based decision support tool. Among the various modelling paradigms, equation-based models and agent-based models are widely used to develop dynamic models of systems. Which is the most appropriate modelling paradigm for a supply chain? In this paper, we seek to address this important question through a well-structured benchmarking process. First, we demonstrate that in the space of models, 'equations' and 'agents' are concepts of a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…An ABDS system can scale much more freely than system dynamics, especially if the model can be scaled using databases. This corresponds to the findings of van Dam et al (2009). However, constructing a similar kind of system dynamics model would have taken less time.…”
Section: Discussionmentioning
confidence: 99%
“…An ABDS system can scale much more freely than system dynamics, especially if the model can be scaled using databases. This corresponds to the findings of van Dam et al (2009). However, constructing a similar kind of system dynamics model would have taken less time.…”
Section: Discussionmentioning
confidence: 99%
“…For stochastic models, when multiple runs of the models are averaged out, it still cannot be concluded that the output will also be the same. But after looking at the definition of the models and how the results are produced, it is possible to get a better understanding of how models will behave under different inputs and different scenarios [24].…”
Section: Implementation Results and Discussionmentioning
confidence: 99%
“…A benchmarking study has been executed in which the agent-based model was compared with an equation-based model of the same supply chain [21]. The aim of the benchmarking study was to compare the modeling paradigms (i.e., the agent-based and equation-based paradigms) and to learn about the advantages and disadvantages of the different approaches.…”
Section: Verification and Validation Of The Modelmentioning
confidence: 99%
“…Modeling the behavior of the agents was based on existing behavioral rules for trading (as also used in the freight hub model from Section 2.3.1), but additional rules had to be implemented for various procurement policies (e.g., forecasting of demand deciding on procurement), scheduling which OperationalConfiguration to use and for the activities of the jetty (which had not been used in earlier models), for example [21]. The new elements can now be shared with other modelers or be re-used in new case studies and as such the new modeling effort has contributed to a larger set of building blocks.…”
Section: Implementation Of the Behavior Of The Agentsmentioning
confidence: 99%
See 1 more Smart Citation